Violência e dominação: o estado, a mídia e a (re)produção dos “despossuídos” - Lachovski, Marilda Aparecida (2021)
The present thesis work, anchored in the perspective of Discourse Analysis, proposes a reflection on the discursivization of violence practices, in and by the media, in a relationship with the State and legal norms. Among the practices of violence, lynching is understood as one of the ways in which “doing justice” is reproduced, and also as a possible place of confrontation, attesting to the attempt to naturalize violence, under the existence and organization of the street’ courts of justice. Through interdiscourse, slavery resonates, legitimizing symbolic violence as an instrument for the efficiency of a regulatory and punitive power, on the one hand for the false tutelage of the State and, on the other, for the population in a pretext of justice, producing the incitement to hatred against certain subjects and social groups. We ask ourselves about the ways in which these street courts are organized, in and by discourse, in and by the media, asking for the devices that regulate these collective organizations, and how they make the modes of domination and exclusion work, ideologically inscribed in the construction of an ideal of nation and citizenship. To this end, we selected five discursive clippings: three cases of lynching that circulated in the media and two series of comments by subjects users/followers of the pages of newspapers Extra and G1, on Facebook, about these cases, in which regularization and repetition produce movements of meanings on “doing justice”, on justifying. Regulation and control, as justifications for lynching, work as part of the domination process, in which skin color and lace are still, as effects of naturalization, what defines, legitimizes and sustains symbolic violence. It is the functioning of the modes of domination and exclusion that affect and cross legal practices in Brazil, (re)producing the emerging portion of “dispossessed” subjects, structuring the social division.